Methanol Extract of Katuk (Sauropus androgynus) Leaves as an Anti-inflammatory Agent: Animal Study in Carrageenan-induced Rat Models of Inflammation - Desy Andari; Farah Ibnu Khan; Safira Idofia Jakfar (Cell and BioPharmaceutical Institute, 2022)
Background: Inflammation is a response in the human body to survive during infection, injury and tissue damage. Acute inflammation causes edema and polymorphonuclear neutrophils (PMNs) release. Sauropus androgynus leaves which contain flavonoids, tannins, saponins, steroids and triterpenoids may have anti-inflammatory properties. These compounds can be extracted with methanol. This research aimed to determine the anti-inflammatory effect of S. androgynus leaves methanol extract (SALME) on carrageenan induced-rats. Materials and methods: True experimental study was conducted using 12 Wistar rats. Rats were induced with carrageenan subcutaneously on the plantar pedis. Carrageenan-induced rats were treated with/without various doses of SALME. Edema volume was measured with a plethysmometer. The plantar pedis tissues were collected and stained with haematoxylin- eosin (HE) staining, then PMNs were observed and counted under a light microscope. All data were analyzed by one-way ANOVA, Bonferroni post hoc test, Pearson correlation and linear regression. Results: SALME had significant effects on the volume of edema (p=0.000) and the number of PMNs (p=0.000). The most effective dose to reduce the edema volume and decrease the PMNs cell number was 37.80 mg/200 g body weight (BW). SALME doses may affect 91.0% of edema volume and 89.2% of PMNs cell number. Edema volume had a significant, robust correlation (92.3%) with PMNs cell number. Conclusion: SALME is confirmed to have an anti-inflammatory activity by reducing the edema volume and decreasing the PMNs cell number. Keywords: Sauropus androgynus, methanol extract, anti-inflamamatory, carrageenan, plantar pedis, rats